Development of audiovisual animation media of learning vocational art music for mentally disabled - Cecep Permana (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2018)
This research was purposed in creating a product of audio visual animation media for teaching music to mentally disabled students at SLB Negeri 2 Padang. This research method was being used the development research. This research was included the research to make a new product in teaching system. This research was used the approach of ADDIE (anasysis, Desain, Develop, Implement, Evaluate) model. The data was being gotten from the interviews observations, literature educations and documentations. The technical analysis of data was being held by using analysis teachnic descriptive qualitative.this technical analysiswas gave the result of the development product in teaching media based on multimedia. Furthermore,it was gave the result test for level of validation and reliable of the pruduct to be implemented in teaching vocational art music at subject of marching bandof Indonesian raya song. The result of this research was being showed the result of learning and creativity thementally disabled students in vocational art music learning. This research also aimed To fullfill the standardize of grade and suitable for completeness study of standardize. Besides that the appearance audio visual animation media was used to increase the concentration, communication and expression in responing the subject so that the ability of the student in vocational art music learning was being developed better.